The Impact Of Competence And Service Placement To Regulatory Work Motivation Air Traffic Of Indonesian Aif Force - Toni Toni; Nugroho B Sukamdani; Toto Hardiyanto (The International Journal of Business Review (The Jobs Review), 2022)
Air traffic controllers, also known as PLLUs, are members of the Indonesian Air Force who are responsible for aviation safety. Personnel of the TNI AU PLLU must be willing to be sent to various TNI AU bases across the area of the Unitary State of the Republic of Indonesia (NKRI). In order to achieve optimal performance, TNI AU PLLU workers must possess high levels of competence and work motivation due to their considerable obligations and responsibilities. In order to achieve optimal performance, TNI AU PLLU workers must possess high levels of competence and work motivation due to their considerable obligations and responsibilities.  A total of 63 respondents were sampled. Using a Likert scale, members of the Indonesian Air Force who work as air traffic controllers were asked a series of questions (questionnaires) as part of an observation technique for collecting data. Analysis of data using the smartPLS 3.0 application yielded the following results; foremost, competency has a strong and favorable impact on work motivation; Second, service placement has a favorable and statistically significant effect on work motivation; Third, competence and office placement have a positive and statistically significant combined effect on work motivation.